Alleviating poverty, intensifying agriculture, and effectively managing natural resources - Pinstrup-Andersen, Per; Pandya-Lorch, Rajul (International Food Policy Research Institute, 1994)
This discussion paper is the first in a series of papers prepared as part of IFPRI's 2020 Vision initiative, which seeks to develop an international consensus on how to meet future world food needs while reducing poverty and protecting the environment. It shows that poverty and environmental degradation in the developing world are inextricably linked with inadequate agricultural intensification. Increased investment in agriculture and poverty alleviation are essential for preventing further resource degradation and for meeting future food needs in a sustainable manner.